Joint optimization for product warranty and preventive maintenance in service supply chain. Issue 1 (July 2021) - Xu, Yingcui; An, Xiangxin; Zhu, Ying; Xia, Tangbin; Miao, Rui
Abstract: Industrial competition has been extended from the traditional price and quality competition to warranty competition, from the single manufacturer competition to the whole supply chain system competition. Existing research mainly focuses on the decision-making problems of warranty period and price. However, with the increasing complexity and safety requirements of CNC machine tools and other engineering equipment, customers have put forward higher requirements for product quality and equipment reliability. In this paper, the equipment product deteriorating with aging is taken as the research object, and a two-level service supply chain profit model under Stackelberg game with strong manufacturer bundled sales of "product + warranty" is constructed. Moreover, the impact of warranty period and preventive maintenance frequency on the equilibrium price of product-service package is discussed. This paper provides a new and scientific approach for the optimization of product service strategy.